KLENENG KEDUK TRADITION (Study of Symbolic, Religious and Socio-Cultural Meanings in the Kledeng Kleduk Tradition) - Triantoro, Drs. Miranu (IJRDO- Journal of Educational Research, 2020)
Almost every region in Indonesia has a tradition. A tradition will continue to be preserved and continue to be preserved if the values ​​contained therein are able to follow the dynamics and demands of the local community. the tradition of kledug kleneng. The tradition of kleneng kleduk is carried out in the event of an eclipse of the sun and a lost child that some people hide by ghosts. In the kleduk kleneng tradition there is a religious value, namely the existence of the ancestors’ trust in forces outside of humans, namely the belief in animism and dynamism. Socio-cultural values ​​describe the attitudes and behavior of people’s lives about the need for cooperation, mutual cooperation, mutual assistance and respect for others. Symbolic values ​​appear in the type of uborampe offerings used for the purposes of salvation, each having its own meaning and function.